UPAYA MENINGKATKAN KINERJA PENJUALAN PRODUK UMKM DI KABUPATEN SUMBAWA MELALUI PENERAPAN DIGITAL MARKETING - Yunita, Fiana Arma; Sudiyarti, Nining (Fakultas Ekonomi dan Manajemen, 2024)
This study aims to determine the effect of digital marketing in improving the sales performance of MSME products in Sumbawa District. The type of this study was associative which aims to examine the effect of implementing digital marketing in improving the sales performance of MSME products in Sumbawa District. The type of data used was quantitative data collected directly by researchers from research respondents using a research instrument in the form of a questionnaire. The sample used as respondents in this study were 91 MSME actors in Sumbawa District. Respondent selection was carried out using non-probability sampling techniques with the simple random sampling method. Data analysis tools were performed using simple linear regression analysis techniques, t test, and the coefficient of determination (R2) test. The results of this study showed that digital marketing had a positive and significant effect on the sales performance of MSME products in Sumbawa District. This means that the higher the level of digital marketing implementation, the higher the sales performance of MSME products in Sumbawa Regency. Conversely, the lower the level of digital marketing implementation, the lower the sales performance of MSME products in Sumbawa Regency. The ability of digital marketing to effect the sales performance of MSME products in Sumbawa Regency was 41.3%, while the remaining of 58.7% was effected by other variables outside this research model, such as market orientation and product innovation.